2007
DOI: 10.1002/ajpa.20615
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Compatibility of microtomographic imaging systems for dental measurements

Abstract: Modern micro-computed tomography techniques allow the accurate visualization of internal dental structures, and are becoming widely used within (paleo-) anthropological dental studies. There exist several types and name brands of microtomographic systems, however, which have been demonstrated to produce images that vary in resolution and signal-to-noise ratio. As a growing body of dental research using disparate microtomographic techniques is likely to continue accumulating, it is imperative that different sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…E-mail: delphine_maret@yahoo.frthree-dimensional (3D) reconstructions coming from 3D images needs to be clearly established. Accuracy has already been assessed 7 by comparing reconstructions using CBCT with those provided by the standard in 3D dental research, micro-CT. [8][9][10][11][12] Similar volumetric measurements were obtained using CBCT with an isotropic voxel size of 76 mm and the reference method, micro-CT, with an isotropic voxel size of 41 mm. 7 The important influence of voxel size on the quality of CBCT images and on scanning and reconstruction times is already acknowledged.…”
Section: Introductionmentioning
confidence: 69%
“…E-mail: delphine_maret@yahoo.frthree-dimensional (3D) reconstructions coming from 3D images needs to be clearly established. Accuracy has already been assessed 7 by comparing reconstructions using CBCT with those provided by the standard in 3D dental research, micro-CT. [8][9][10][11][12] Similar volumetric measurements were obtained using CBCT with an isotropic voxel size of 76 mm and the reference method, micro-CT, with an isotropic voxel size of 41 mm. 7 The important influence of voxel size on the quality of CBCT images and on scanning and reconstruction times is already acknowledged.…”
Section: Introductionmentioning
confidence: 69%
“…Micro CT can provide highly accurate and precise assessment of internal dental structures and root canal morphology [37][38][39][40] and has been considered as a reference standard in dental liner and volumetric measurements [41][42][43][44]. In the present study, a significant difference was observed between the pulp volumes obtained from Micro CT and CBCT images (p = 0.024), but the average difference is relatively small (2.3%) when compared it to the difference reported in a previous study (maximally 21%) [22].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, microCT has been used extensively to study tooth, for example, carious lesions , root canal geometry in whole teeth (Dowker et al, 1997), fracture processes in dentin (Kruzic et al, 2003), mineral levels in enamel (Dowker et al, 2004(Dowker et al, , 2006 and de-/re-mineralization of enamel Vieira et al, 2006). Similar to numerous comparisons on bone and inorganic materials, some of which are reviewed by Stock (submitted for publication), synchrotron and laboratory microCT systems have been compared for the study of tooth (Olejniciczak et al, 2007). Although tooth specimens spanning the DEJ have been imaged with tube-based microCT systems (e.g.…”
Section: Introductionmentioning
confidence: 98%